2022
DOI: 10.1155/2022/8778430
|View full text |Cite
|
Sign up to set email alerts
|

Change in Police Attendance at Overdose Events following Implementation of a Police Non-Notification Policy in British Columbia

Abstract: Introduction. Bystanders at overdose events often hesitate to call 911 due to fear of police involvement. To address this, in 2016, British Columbia Emergency Health Services (BCEHS) introduced a policy to not routinely inform police of overdose events. This study explores change in police attended overdose events after the policy was implemented. Methods. Data on police attended overdose events were derived from naloxone administration forms in BC’s Take-Home Naloxone (THN) kits returned before and after the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Additionally, people who did not currently know someone who non-medically used opioids may have been influenced by societal stigma associated with the overdose epidemic, impacting their knowledge and attitude about opioid addiction 29 40 41. Previous research has linked higher levels of stigma toward people who use prescription opioids to increased support for punitive policies, less support for public health and prevention measures, and a decreased motivation to interact with people who use opioids 29 31 41. Like the findings in our study, a recent study among US young adults also found that people with less personal experience with opioid use disorder were more likely to exhibit more negative attitudes towards opioid use 40…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Additionally, people who did not currently know someone who non-medically used opioids may have been influenced by societal stigma associated with the overdose epidemic, impacting their knowledge and attitude about opioid addiction 29 40 41. Previous research has linked higher levels of stigma toward people who use prescription opioids to increased support for punitive policies, less support for public health and prevention measures, and a decreased motivation to interact with people who use opioids 29 31 41. Like the findings in our study, a recent study among US young adults also found that people with less personal experience with opioid use disorder were more likely to exhibit more negative attitudes towards opioid use 40…”
Section: Discussionsupporting
confidence: 60%
“…Individuals who had more positive attitude toward and reduced stigma towards helping someone with an opioid addiction and skills to help someone with an opioid addiction were more likely to exhibit greater helping behaviour 29 30. In addition to attitude and skills, research has shown that support from healthcare providers and family is associated with increased likelihood of helping someone with opioid addiction 31 32. Outside of individual and interpersonal factors, environmental factors, such as community, faith-based and healthcare organisations, that support helping behaviour have also been shown as important factors to address opioid non-medical use 33.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, this requires an individual to see the event, which could be a function of context-specific outdoor/indoor usage and the population density of a region. Secondly, this requires the bystander to have a certain level of trust in law enforcement which also may have neighbourhood-level variations ( Mehta et al, 2022 , Smiley-McDonald et al, 2022 , Wagner et al, 2019 ). Without detailed data on opioid usage rates at the DA-level, we feel that this proxy is reasonable for capturing general trends in opioid usage across the city.…”
Section: Discussionmentioning
confidence: 99%
“…By training first responders in harm reduction and post-overdose referral options, people who refuse transportation to a hospital may be more likely to receive the care they prefer at another type of service agency 18 . People who experience overdose, as well as their friends and family, may be more comfortable contacting non-police emergency responders and community-based responders 19,20 .…”
Section: Discussionmentioning
confidence: 99%